Compaction of granular graphite in a vertically vibrating container with restricted geometry - Gerasimov, O.I.; Idomskyy, V.A.; Schram, P.P.-J.M. (Condensed Matter Physics, 2001)
The compaction of vertically vibrating granular materials (highly dissipative media composed of macroscopic grains that interact by means of contact forces) with restricted geometry is examined stroboscopically. Possible interpretation of the observed picture of compaction is discussed in particular by means of the nonequilibrium (nonergodic) states predicted in hydrodynamics of one-dimensional system of inelastic particles [1] as well as described in dynamics of 1D chemically reacted lattice model [2–5]. Вивчаються стробоскопічно ущільнення вертикально вібруючих гранульованих матеріалів (високо дисипативного середовища, що складається з макроскопічних зерен, взаємодіючих контактно) з обмеженою геометрією. Можлива інтерпретація спостережуваної картини обговорюється, зокрема, з допомогою нерівноважних (неергодичних) станів, передбачених в гідродинаміці одновимірних систем нееластичних частинок [1] і описаних в динаміці одновимірної хімічно-активної граткової моделі [2–5].